THE ADVERSE DRUG REACTIONS OF INTERMITTENT AND DAILY REGIMENS IN THE TREATMENT OF THE INTENSIVE PHASE OF TUBERCULOSIS - Eline mathew, Anu; R, Vishnu; Baby, Minu; RG, ANAND (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: To study the adverse drug reactions (ADRs) of intermittent and daily anti-tubercular therapy in intensive phase (IP), in patients attending the RNTCP unit, Government Medical College (GMC), Thrissur. Methods: A prospective observational study was done at the RNTCP unit, GMC, Thrissur, during October 2016-2017. Two hundred and thirty-five patients satisfying inclusion criteria, receiving anti-tubercular therapy as intermittent and daily regimens were selected. Demographic data, risk factors, comorbidities, and investigations were recorded and patients were followed up for IP. Results of investigations, treatment outcome, and ADRs recorded after IP. ADRs were monitored and its causality and severity were assessed. Data were entered in MS Excel and analyzed using SPSS. Qualitative variables are represented as proportions and quantitative as mean and standard deviation. Associations were analyzed using appropriate statistical tests. Analysis was performed using paired t-test p<0.05 taken as significant. Results: Orange-red urine and secretions were the most common ADR, followed by nausea, fatigue, heartburn, etc. Significant increase in random blood sugar, renal function tests (RFTs), and liver function tests (LFT) after treatment, then before noticed. 84.4% of patients from the daily group and 78% of patients from the intermittent group experienced ADRs. Causality was assessed using Naranjo’s algorithm and severity using a modified Hartwig and Siegel scale. Conclusion: The majority of patients developed ADRs, which were mild and managed symptomatically. Some reactions required alteration of therapy, reduction of drug dose, or change of suspected drug. To conclude, meticulous monitoring of ADRs in patients on anti-tubercular drugs is mandatory.